Adsorption of Lead from Aqueous Solution by Manganese Ferrite Nanoparticles - Aswin Sidhaarth, K.R.; Jeyanthi, J. (Asian Journal of Chemistry, 2013)
The adsorption of lead onto manganese ferrite nanoparticles was investigated. The adsorption characteristics and lead removal efficiency of the adsorbent have been determined by investigating the influence of operating variables such as contact time, dosage, pH, concentration of lead and agitation speed. The graphical correlation of various adsorption isotherm models like Langmuir, Freundlich and Tempkin have been used to evaluate the ongoing adsorption. The isotherm and kinetic studies suggest that the process follows Langmuir, pseudo first and second order kinetics. Column studies were also performed to test the ground efficiency of manganese ferrite nanoparticles by varying the depth and the results were subjected to Thomson and Yoon Nelson modeling. From both the modeling studies it was observed that the rate of removal of lead decreased from 3.350 to 1.525 and 18.53 to 9.19 mg/g as the filtering depth in the column increases.